2022
DOI: 10.3389/fpubh.2022.814328
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategy, Life Style and Health Status During Phase 3 of Indian National Lockdown for COVID-19 Pandemic—A Pan-India Survey

Abstract: The implementation of timely COVID-19 pan-India lockdown posed challenges to the lifestyle. We looked at the impact of lifestyle on health status during the lockdown in India. A self-rated scale, COVID Health Assessment Scale (CHAS) was circulated to evaluate the physical health or endurance, mental health i.e. anxiety and stress, and coping ability of the individuals under lockdown. This is a pan-India cross-sectional survey study. CHAS was designed by 11 experts in 3 Delphi rounds (CVR = 0.85) and was circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A recent study conducted in a large university of the Mid-Atlantic region in the United States showed that extraversion and avoidance coping style moderated the effect of COVID-19 stressful life events on mental health 57 . Moreover, a positive correlation was observed between positive coping style and less psychological distress in Indian population during lockdown 58 . Furthermore, when an individual has more psychological capitals during the grow-up, it is easier for him/her to take a positive coping style to nd solutions with more positive optimism when facing challenges 59 , promoting the individual's health.…”
Section: Discussionmentioning
confidence: 81%
“…A recent study conducted in a large university of the Mid-Atlantic region in the United States showed that extraversion and avoidance coping style moderated the effect of COVID-19 stressful life events on mental health 57 . Moreover, a positive correlation was observed between positive coping style and less psychological distress in Indian population during lockdown 58 . Furthermore, when an individual has more psychological capitals during the grow-up, it is easier for him/her to take a positive coping style to nd solutions with more positive optimism when facing challenges 59 , promoting the individual's health.…”
Section: Discussionmentioning
confidence: 81%
“… 57 Moreover, a positive correlation was observed between positive coping style and less psychological distress in Indian population during lockdown. 58 Furthermore, when an individual has more psychological capitals during the grow-up, it is easier for him/her to take a positive coping style to find solutions with more positive optimism when facing challenges, 59 promoting the individual’s health. In this study, we found that the psychological capital was a major effect on self-rated health with a statistically significant three-way interaction analysis.…”
Section: Discussionmentioning
confidence: 99%